Display process compatible accurate graphene patterning for OLED applications. (13th December 2017) - Shin, Jin-Wook; Han, Jun-Han; Cho, Hyunsu; Moon, Jaehyun; Kwon, Byoung-Hwa; Cho, Seungmin; Yoon, Taeshik; Kim, Taek-Soo; Suemitsu, Maki; Lee, Jeong-Ik; Cho, Nam Sung
Abstract: Graphene film can be used as transparent electrodes in display and optoelectronic applications. However, achieving residue free graphene film pixel arrays with geometrical precision on large area has been a difficult challenge. By utilizing the liquid bridging concept, we realized photolithographic patterning of graphene film with dimensional correctness and absence of surface contaminant. On a glass substrate of 100  ×  100 mm 2 size, we demonstrate our patterning method to fabricate an addressable two-color OLED module of which graphene film pixel size is 170  ×  300 µ m 2 . Our results strongly suggest graphene film as a serviceable component in commercial display products. The flexible and foldable display applications are expected to be main beneficiaries of our method.